Bibi Fatima and the king's sons - Sulṭān ibn Muḥammad al-Qāsimī, Ruler of Shāriqah, 1939- (Al Qasimi Publications, 2018)
"This is the story of an ambitious woman who clings to the faltering rule of the kings of Hormuz under the Portuguese occupation. The novel offers a detailed description of social life in Hormuz, while touching upon the military, political and economic situation prevailing at the time."--Page 5